2021
DOI: 10.3390/app11104431
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Table Tests of Lead Inserted Small-Sized Laminated Rubber Bearing for Nuclear Component Seismic Isolation

Abstract: To assure seismic isolation performance against design and beyond design basis earthquakes in the nuclear facility components, the lead inserted small-sized laminated rubber bearings (LRB), which has a 10 kN vertical design load, have been designed and quasi-statically tested to validate their design mechanical properties in previous studies. Following this study, the seismic shaking tests of these full-scale LRBs are performed and discussed in this paper with the dummy mass system to investigate actual seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Numerous experimental research has been conducted in order to determine the mechanical characteristics of this type of LRB. It has been confirmed that the lead core provides an adequate level of energy dissipation [4,[10][11][12][13]. The numerical models for the analysis of the properties of a LRB were also developed [12,[14][15][16][17].…”
Section: Figure 1 Characteristic Section and Basic Parts Of Lead Rubb...mentioning
confidence: 91%
“…Numerous experimental research has been conducted in order to determine the mechanical characteristics of this type of LRB. It has been confirmed that the lead core provides an adequate level of energy dissipation [4,[10][11][12][13]. The numerical models for the analysis of the properties of a LRB were also developed [12,[14][15][16][17].…”
Section: Figure 1 Characteristic Section and Basic Parts Of Lead Rubb...mentioning
confidence: 91%
“…Recently, the number of studies on the development of different seismic base isolator systems has increased in South Korea. A common standard practice in the design and verification process of base isolation systems has been adopted for this study, which is under draft stage [38,39].…”
Section: Verification Of Rfb Devicesmentioning
confidence: 99%
“…The 3D seismic isolator being developed in this study is intended to be applied to individual facilities of nuclear power plants where severe vertical earthquake response amplification is expected. To this end, the horizontal seismic isolator uses a lead-inserted small LRB with proven stability and seismic isolation performance [16,17], and a springdamper-based vertical seismic isolator is mounted on the top of the LRB.…”
Section: Configurations and Dimensionsmentioning
confidence: 99%
“…The goal of this study is to develop a 3D seismic isolator for individual nuclear power plant facilities that are relatively easy to install and maintain when compared with the whole building seismic isolation design. For this purpose, a study was conducted on a vertical seismic isolation device having a spring and a steel damper that can be integrally combined with lead-inserted small LRBs for horizontal seismic isolation developed for individual facilities in nuclear power plants [16,17].…”
Section: Introductionmentioning
confidence: 99%